Application of project-driven dual-teacher teaching model in the practical teaching of biomedicine - Bihua Zhou; Sinian Liu; Dongliang Song; Yingsong Wu; Yao Chen (BMC Medical Education)
Abstract Background This research sought to assess the impact of a project-oriented dual-teacher internship model in comparison to a conventional internship model within the context of biotechnology major internships. Methods This study employed a comparative research approach, involving 171 interns from the biotechnology major at a specific higher education institution. Of these, 101 interns underwent traditional internships, while 70 participated in a dual-teacher internship, grounded in the school-enterprise collaborative innovation project. Data collection was achieved through questionnaires and interviews, aimed at assessing the efficacy of various internship modalities. Results Students who undertook the dual-teacher internship exhibited enhanced satisfaction, particularly in relation to their overall experience, knowledge verification, and the transformation of theoretical skills.Furthermore, the students who participated in the double teacher practice were more inclined to continue education and self-improvement. Conclusions The findings of this study indicate that the project-driven dual-teacher internship approach yields superior educational outcomes compared to the conventional internship model in the field of biotechnology.